In situ assessment of the roughness of a uniformly eroded cylindrical magnetron target. (April 2017) - Arif, Muhammad; Ernstbrunner, Thomas; Eisenmenger-Sittner, C.
Abstract: We present an experimental approach for the in situ characterization of the surface roughness of an eroded magnetron target based on the reflectance pattern of a laser beam. The surface of the eroded region was modeled as a random arrangement of tilted plane facets with large surface extensions as compared to the wavelength of the laser. A simple algorithm was used to reconstruct surface profiles form the reflected intensity values from the eroded surface. The surface profiles of Al, Cu and Ti targets were reconstructed under high vacuum conditions without disturbing the processing parameters of the magnetron sputtering plant. From these generated profiles, the roughness parameters, root mean square roughness, correlation length, skewness and kurtosis of different target materials were calculated by this in situ technique. The results measured with this in situ technique are in good agreement with comparable measurements using a mechanical profilometer outside the sputtering system. However, some deviation was observed for surfaces with higher roughness and mean tilt angles. This method can be used for in situ monitoring of sputter targets to extract the surface features which may correlate with thin film properties and may precede dangerous events like target melting or other catastrophic failures. Highlights: The surface roughness of an eroded cylindrical magnetron target was characterized by a laser beam. A simple algorithm was used to generate surface profiles form intensity values, reflected from the facets of the eroded target surface. The roughness parameters of the Al, Cu and Ti targets were calculated from the generated profiles. The temporal behaviour of roughness evolution upon erosion was examined by this in situ technique.